Increased Risk of Central Serous Chorioretinopathy among Patients with Nonorganic Sleep Disturbance. (12th February 2020) - Tien, Peng-Tai; Lai, Chien-Yu; Lin, Chun-Ju; Chen, Wen-Lu; Lin, Po-Kang; Muo, Chih-Hsin; Tsai, Yi-Yu; Wan, Lei; Ho, Wen-Chao; Lin, Hui-Ju
Abstract : Purpose . Patients with central serous chorioretinopathy (CSC) typically present with acute visual impairment and metamorphopsia. The disease previously has been associated with psychological stress. Population-based cohort studies on the risk of CSC among patients with nonorganic sleep disturbance (NOSD) are limited. An early sign of psychiatric disorder was probably sleep disturbance. Furthermore, psychological stress may be caused by sleep disturbance. We investigated the relationship between NOSD and the incidence of CSC. Design . Longitudinal cohort study. Participants . We used the Longitudinal Health Insurance Database and collected the data of 53, 743 NOSD patients without CSC between 2000 and 2005 as the study group. Four-fold controls were selected randomly from those without neither sleep disturbance nor a CSC history with frequency matching of age, sex, and index-year. Methods . The difference in sex, age group, comorbidities, and steroid use between the two groups was analyzed by the χ 2 test. Cox-proportional hazard regression was utilized to estimate the hazard ratio (HR) and 95% confidence intervals (95% CI) for comparison of the two groups. Kaplan–Meier analysis was applied to measure the cumulative incidence of CSC. Furthermore, the log-rank test was used to test the incidence difference between the two groups. Main Outcome Measures . The incidence rate of CSC in the following years until 2011 was detected. Results . During a mean follow-up of 7.36 ± 2.88 years, NOSD patients had a higher incidence of CSC than the controls (3.10 vs. 1.86 per 10, 000 person-years; adjusted HR, 1.65; 95% CI, 1.34–2.02). Men had a higher risk of CSC than women. Sensitivity analyses stratified by sex, age group, or comorbidity condition showed consistently that NOSD patients had a higher risk of CSC than their controls. Dose-response showed that higher NOSD severity had even higher CSC risk. Conclusions . NOSD is an independent indicator for the increased risk of subsequent CSC development.